2011
DOI: 10.1159/000327431
|View full text |Cite
|
Sign up to set email alerts
|

Outer Retinal Microstructure in a Case of Acute Idiopathic Blind Spot Enlargement Syndrome

Abstract: Purpose: To present a patient with acute idiopathic blind spot enlargement syndrome who had abnormal changes in the outer retinal microstructure limited to areas with reduced responses on multifocal electroretinograms as well as to the area involving a scotoma. Methods and Results: We report the case of a 44-year-old man who developed an arcuate scotoma which was associated with a physiological blind spot in the left eye. The ophthalmoscopic, fluorescein angiographic, and full-field electroretinogram findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0
15

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(41 citation statements)
references
References 17 publications
0
26
0
15
Order By: Relevance
“…Several investigators have examined the correlation between the integrity of the microstructures and the BCVA in eyes with a macular hole, occult macular dystrophy and the acute zonal occult outer retinopathy complex 4 8 14 15 18 19. Recently, a significant correlation was found between foveal function, for example, the VA, and the quantitative parameters of the photoreceptor microstructures 10 13 14.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators have examined the correlation between the integrity of the microstructures and the BCVA in eyes with a macular hole, occult macular dystrophy and the acute zonal occult outer retinopathy complex 4 8 14 15 18 19. Recently, a significant correlation was found between foveal function, for example, the VA, and the quantitative parameters of the photoreceptor microstructures 10 13 14.…”
Section: Discussionmentioning
confidence: 99%
“…5 Our observation of transient loss of ELM in the absence of cone outer segment tip line may represent a transient damage that occurs early in the course of the diseases. The integrity of external FIGURE 1.…”
mentioning
confidence: 74%
“…Optical coherence tomographic image showing that the IS/OS line, the middle cone outer segment tip (COST) line between the IS/OS line and the retinal pigment epithelium (RPE) are discernible in the control subject, but the IS/OS line is relative obscure and the COST line is absent in the patient. Modified and reproduced from (Hanazono et al, 2011) with permission from Dove Medical Press Ltd.…”
Section: Occult Retinal Lesionsmentioning
confidence: 99%
“…(Fletcher et al, 1988;Gass 2003) The pathological site for the visual field abnormalities is not the optic nerve but the retina, and the diagnosis is made from the mfERG findings ( Figure 8). (Sugahara et al, 2011) The spectral domain OCT (SD-OCT) images showed abnormalities in the microstructures of the outer retina, e.g., disruption or loss of the external limiting membrane (ELM), the IS/OS line, and/or an absence of the COST line in the areas of the visual field defects ( Figure 9). (Spaide et al, 2008;Sugahara et al, 2011;Tsunoda et al, 2011) It is still under discussion whether fmERGs are better than OCT in detecting the early abnormalities in OMD and in monitoring the changes in the severity or stage of OMD and AZOOR-complex.…”
Section: Occult Retinal Lesionsmentioning
confidence: 99%
See 1 more Smart Citation